Pro-Muslim Policies in Cambodia: Bureaucratizing Halal And Hijab in Muslim Minority Country - Khaidir Hasram (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This paper explores the dynamics of Pro-Muslim policies in the Kingdom of Cambodia, specifically related to halal institutionalization and the legalization of the hijab. Both are basic needs (dharuriyat) in Islamic Law, although the second is debatable. According to most early-period scholars (ulama klasik), these two policies could only be fulfilled in an Islamic state. Instead, the Cambodian Royal Government issued two policies in favour of Muslims practicing both needs. This research is qualitative research that uses an anthropological approach. Researchers collected data through observation, in-depth interviews, and documentation on policy documents, news, and articles that can be trusted. Interviews took place non-formally, face-to-face, and online via the internet. This paper argues that the pro-Muslim policies issued provide halal assurance for the consumption of the Muslims in the country (2% of the total population) and potentially improve the their socio-economy in the food and beverage industry and tourism. The legalization of the hijab guarantees that Muslim women can engage in public spaces freely without worrying about discrimination because of their identity and what they wear. Tulisan ini mengeksplorasi dinamika kebijakan Pro-Muslim di Negara Kerajaan Kamboja, secara spesifik terkait dengan kebijakan pelembagaan halal dan legalisasi hijab. Keduanya merupakan kebutuhan dasar (dharuriyat) dalam Hukum Islam, meskipun yang kedua masih diperdebatkan. Menurut mayoritas ulama periode awal, dua kebijakan ini hanya bisa terpenuhi di negara Islam. Sebaliknya, Pemerintah Kerajaan Kamboja,yang secara resmi menganut Buddhisme sebagai agama resmi negara, mengeluarkan dua kebijakan yang mendukung Muslim dengan mudah mengamalkan kedua kebutuhan tersebut. Penelitian ini adalah penelitian kualitatif yang menggunakan pendekatan antropologis. Peneliti mengumpulkan data-data melalui observasi, indepth-interview, dan dokumentasi terhadap dokumen kebijakan, berita, dan artikel yang bisa dipercaya. Interview berlangsung secara non-formal, melalui tatap muka dan online melalui internet. Tulisan ini berpendapat bahwa kebijakan pro-Muslim yang dikeluarkan memberikan jaminan kepastian halal untuk konsumsi 2.0 persen Muslim di negara tersebut, serta berpotensi meningkatkan perekonomian Muslim dalam industri makanan dan minuman, serta pariwisata. Legalisasi hijab memberikan jaminan kepada perempuan Muslim untuk mampu terlibat dalam ruang publik dengan bebas tanpa menghawatirkan diskriminasi karena identitas dan apa yang ia pakai.